Corrective Nasal Surgery after Maxillomandibular Advancement for Obstructive Sleep Apnea: Experience from 379 Cases. (July 2017) - Liu, Stanley Yung-Chuan; Lee, Pi-Jung; Awad, Michael; Riley, Robert W.; Zaghi, Soroush
Objective: Efficacy of maxillomandibular advancement (MMA) in the treatment of obstructive sleep apnea (OSA) is associated with degree of maxillary advancement. Large maxillary advancement leads to profound changes of the nasolabial region. We present the incidence and indications of post-MMA corrective nasal surgery in a large cohort. Study Design: Case series with chart review. Setting: University medical center. Subjects and Methods: A total of 379 subjects with OSA underwent MMA at Stanford Hospital (surgeons: S.Y.L., R.W.R.) from August 1992 to December 2015. Data were collected on age, sex, American Society of Anesthesiologists score, polysomnography parameters, and history of nasal surgery. Primary outcome parameters were the incidence and indications of post-MMA corrective nasal surgery. Results: Of 379 subjects, the surgical success rate was 76.3% based on the change in respiratory disturbance index. Seventy-one subjects (18.7%) underwent corrective nasal surgery after MMA, whereas 48 underwent functional nasal surgery and 23 underwent both functional and aesthetic nasal surgery. Lower oxygen saturation nadir and higher baseline respiratory disturbance index were associated with increased likelihood of post-MMA corrective nasal surgery. Conclusion: MMA surgical success is associated with degree of maxillary advancement, which is especially significant in patients with severe OSA. Patients must be counseled on its impact in nasal function and aesthetics. Our series, the largest to date to address this question, suggests that the incidence of post-MMA corrective nasal surgery is at least 18.7%. Prospectively, refinement in MMA techniques is needed to minimize postoperative compromise in nasal form and function.